2018
DOI: 10.1088/2399-6528/aac797
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling time in attosecond experiment for hydrogen atom

Abstract: Tunneling and tunneling time are hot debated and very interesting issues because of their fundamental role in the quantum mechanics. The measurement of the tunneling time in today's attosecond and strong field (low-frequency) experiments, despite its controversial discussion offers a fruitful opportunity to understand the time measurement and the role of time in quantum mechanics. In previous work Kullie (2015 Phys. Rev. A 92, 052118), we suggested a model and derived a simple relation to calculate the tunneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
5
5
0
Order By: Relevance
“…In previous works [1][2][3], we presented a tunneling model and a formula to calculate the tunneling time (T-time) by exploiting the time-energy uncertainty relation (TEUR), precisely that time and energy are a (Heisenberg) conjugate pair. Our T-time is in good agreement with the attosecond (angular streaking) experiment for He-atom [1] with the experimental finding of Eckle et al [4][5][6], and for hydrogen atoms [7] with the experimental finding of Sainadh et al [8]. Our model presents a real T-time picture or a delay time with respect to the ionization time at atomic field strength F a (see below, compare Figure 1).…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…In previous works [1][2][3], we presented a tunneling model and a formula to calculate the tunneling time (T-time) by exploiting the time-energy uncertainty relation (TEUR), precisely that time and energy are a (Heisenberg) conjugate pair. Our T-time is in good agreement with the attosecond (angular streaking) experiment for He-atom [1] with the experimental finding of Eckle et al [4][5][6], and for hydrogen atoms [7] with the experimental finding of Sainadh et al [8]. Our model presents a real T-time picture or a delay time with respect to the ionization time at atomic field strength F a (see below, compare Figure 1).…”
Section: Introductionsupporting
confidence: 90%
“…Hence, they support the point of view that T-time, i.e., the time to traverse the barrier region, is an imaginary quantity. In [7], we found that the measured data in the experiment with H-atom of Sainadh et al and the accompanied NITDSE [8,49] fits very well to our real T-time picture (Equation (7)). Solely the factor of (1/2) is still unclear; it is absent in the experimental data of Sainadh et al [8,49], unlike the data of Landsman et al [4] for the He atom, as discussed in Sections 3 and 4.…”
Section: Attoclock and Tunneling Time In Strong Field Interactionsupporting
confidence: 77%
See 3 more Smart Citations